2002
DOI: 10.1091/mbc.e02-03-0122
|View full text |Cite
|
Sign up to set email alerts
|

Clastosome: A Subtype of Nuclear Body Enriched in 19S and 20S Proteasomes, Ubiquitin, and Protein Substrates of Proteasome

Abstract: Nuclear bodies represent a heterogeneous class of nuclear structures. Herein, we describe that a subset of nuclear bodies is highly enriched in components of the ubiquitin-proteasome pathway of proteolysis. We coined the term clastosome (from the Greek klastos, broken and soma, body) to refer to this type of nuclear body. Clastosomes contain a high concentration of 1) ubiquitin conjugates, 2) the proteolytically active 20S core and the 19S regulatory complexes of the 26S proteasome, and 3) protein substrates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 69 publications
11
97
0
Order By: Relevance
“…First, Myc was found to concentrate on PML NBs upon inhibition of the proteasome (Smith et al, 2004). Second, proteasomal activity and proteasomal subunits were found to be associated with the PML NB (Lafarga et al, 2002;Rockel et al, 2005). In line with this, we found the interactions between endogenous Myc and PML proteins to be most evident after inhibition of the proteasome.…”
Section: Discussionsupporting
confidence: 82%
“…First, Myc was found to concentrate on PML NBs upon inhibition of the proteasome (Smith et al, 2004). Second, proteasomal activity and proteasomal subunits were found to be associated with the PML NB (Lafarga et al, 2002;Rockel et al, 2005). In line with this, we found the interactions between endogenous Myc and PML proteins to be most evident after inhibition of the proteasome.…”
Section: Discussionsupporting
confidence: 82%
“…Some experiments showed that the low expression of some anti-oncogene including p53, p27 kip1 in tumor cells was associated with the increasing activity of ubiquitin proteasome which leads to degradation of expression products of anti-oncogene, and have proved that deubiquitination of p53 is an important pathway for p53 stabilization [11,12] . Moreover, the degradation accommodation of some transcription factors was regulated by UPP, such as NF-κB, c-fos, c-jun, c-mos, c-myc and MATa [13][14][15][16][17] . So UPP is closely associated with the occurrence and development of malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It is supported by the facts that SUMO-1 molecules aggregate in ND10 and ND10 might be the hot sites for SUMOylation, that the acetylation and phosphorylation of p53 at PML bodies enhance the activity of p53 [16,81,82] , and that the 19S and 20S proteasome subunits localize at some PML bodies [83] .…”
Section: Hotspot Modelmentioning
confidence: 93%